Explaining Self‐Interested Behavior of Public‐Spirited Policy Makers. (30th August 2017) - Zamir, Eyal; Sulitzeanu‐Kenan, Raanan
Abstract : Public choice theory (PCT) has had a powerful influence on political science and, to a lesser extent, public administration. Based on the premise that public officials are rational maximizers of their own utility, PCT has a quite successful record of correctly predicting governmental decisions and policies. This success is puzzling in light of behavioral findings showing that officials do not necessarily seek to maximize their own utility. Drawing on recent advances in behavioral ethics, this article offers a new behavioral foundation for PCT's predictions by delineating the psychological processes that lead well‐intentioned people to violate moral and social norms. It reviews the relevant findings of behavioral ethics, analyzes their theoretical and policy implications for officials' decision making, and sets an agenda for future research.